Los derechos de la generación electrónica en el ámbito laboral - Aba Catoira, Ana (Revista de Derecho, 2019)
The aim of this paper is to provide readers with the legal situation of the exercise of workers’ fundamental rights through electronic means. The idea is to contextualize the traditional conflict between the workers’ rights and the entrepreneurial control faculties in a framework characterized by the use of Information and Communication Technologies to communicate, work and produce. The absence of specific regulation in this matter is a source of constant conflicts which courts have had to resolve due to the numerous litigations posed by the imposing of disciplinary measures for the improper and abusive use of these tools in the work place.